Energy performances of intensive and extensive short rotation cropping systems for woody biomass production in the EU. (January 2015) - Njakou Djomo, S.; Ac, A.; Zenone, T.; De Groote, T.; Bergante, S.; Facciotto, G.; Sixto, H.; Ciria Ciria, P.; Weger, J.; Ceulemans, R.
Abstract: One of the strategies to ensure energy security and to mitigate climate change in the European Union (EU) is the establishment and the use of short rotation woody crops (SRWCs) for the production of renewable energy. SRWCs are cultivated in the EU under different management systems. Addressing the energy security problems through SRWCs requires management systems that maximize the net energy yield per unit land area. We assembled and evaluated on-farm data from within the EU, (i) to understand the relationship between the SRWC yields and spatial distribution of precipitation, as well as the relationship between SRWC yield and the planting density, and (ii) to investigate whether extensively managed SRWC systems are more energy efficient than their intensively managed counterparts. We found that SRWC yield ranged from 1.3 to 24 t ha −1  y −1 (mean 9.3±4.2 t ha −1  y −1 ) across sites. We looked for, but did not find a relationship between yield and annual precipitation as well as between yield and planting density. The energy inputs of extensively managed SRWC systems ranged from 3 to 8 GJ ha −1  y −1 whereas the energy ratio (i.e. energy output to energy input ratio) varied from 9 to 29. Although energy inputs (3–16 GJ ha −1 y −1 ) were larger in most cases than those of extensively managed SRWC systems, intensively managed SRWC systems in the EU had higher energy ratios, i.e. between 15 and 62. The low energy ratio of extensively managed SRWC systems reflected their lower biomass yield per unit area. Switching from intensively managed SRWC systems to extensively managed ones thus creates an energy gap, and will require more arable land to be brought into production to compensate for the yield loss. Consequently, extensification is not the most appropriate path to the success of the wide scale deployment of SRWC for bioenergy production in the EU.